The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cjas.1586
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond the mechanistic structures: The role of inclusive leadership in developing change‐oriented organizational citizenship behaviour

Abstract: In this study, we explore the relationship between inclusive leadership and changeoriented organizational citizenship behaviour (OCB) with the mediating roles of behavioural integrity and trust in leadership. Data were collected from 151 supervisor-subordinate dyads from small and medium enterprises in Pakistan. The results revealed that inclusive leadership is positively related to change-oriented OCB. Our study reaffirms the indirect effect of the inclusive leadership on changeoriented OCB via behavioural in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Brown and Creegau, 2008) as well as higher levels of commitment to change (Neubert and Cady, 2001). Likewise, Younas et al. (2021) suggest that inclusive leadership is positively related to change-oriented organizational citizenship behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown and Creegau, 2008) as well as higher levels of commitment to change (Neubert and Cady, 2001). Likewise, Younas et al. (2021) suggest that inclusive leadership is positively related to change-oriented organizational citizenship behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…, 2010). For example, Younas et al. (2021) quite recently have found that inclusive leadership is positively associated with change-oriented organizational citizenship behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2018; Tran and Choi, 2019). However, despite emerging empirical support, thus far, research has remained elusive on the mechanism linking inclusive leadership to prosocial behaviors such as OCB (Shore and Chung, 2022; Younas et al. , 2021).…”
mentioning
confidence: 99%
“…Employee resilience as a moderator between job crafting and change-oriented OCB Past literature examined a set of contextual predictors that influence change-oriented OCB (e.g.,Chiaburu et al, 2022;L opez-Dom ınguez et al, 2013;Younas et al, 2021). However, existent literature shows minimal studies that investigated the potential psychological mechanisms through which contextual factors influence employees' change-oriented OCB.…”
mentioning
confidence: 99%